Aspergilli Response to Benzalkonium Chloride and Novel-Synthesized Fullerenol/Benzalkonium Chloride Nanocomposite - Nikola Unković; Milica Ljaljević Grbić; Miloš Stupar; Jelena Vukojević; Vesna Janković; Danica Jović; Aleksandar Djordjević (The Scientific World Journal)
A comprehensive comparative analysis of antifungal potential of benzalkonium chloride and newly synthesized fullerenol/benzalkonium chloride nanocomposite was conducted to assess the possible impact of carbon-based nanocarrier on antimicrobial properties of the commonly used biocide. Physical characterization of synthesized nanocomposite showed zeta potential of +37.4 mV and inhomogeneous particles size distribution, with nanocomposite particles’ dimensions within 30–143 nm and maximum number of particles at 44 nm. The effect of pure and fullerenol nanocarrier-bound biocide was evaluated in eight Aspergillus species. In mycelial growth assay, nanocomposite was more potent, as fungicidal effect of 1.04/0.6 μg mL−1 was obtained in all but one of the isolates (A. niger), while proportional concentration of pure biocide (0.6 μg mL−1) completely inhibited mycelial growth of only three Aspergillus species. However, conidia appear to be less susceptible to nanocomposite treatment, as lower fungistatic (MIC) and fungicidal (MFC) concentrations were obtained with biocide alone (MIC in range from 0.03 to 0.15 μg mL−1 and MFC from 0.075 to 0.45 μg mL−1). To a different degree, both substances stimulated aflatoxin B1 production and inhibited ochratoxin A synthesis. Very low mycelium biomass yield, in range from 1.0 to 3.0 mg dry weight, was documented in both biocide and nanocomposite enriched medium.